"Double duck" nasolabial lifting Lifting nasolabial com realce do vermelhão - Vera Lucia Nocchi Cardim; Alessandra dos Santos Silva; Rolf Lucas Salomons; Rodrigo de Faria Valle Dornelles; José Orlofe de Souza Blom; Adriano de Lima e Silva (Revista Brasileira de Cirurgia Plástica, 2011)
BACKGROUND: During aging, the vermilion border of the upper lip wrinkles, stretches, and inverts because of the sphincteric action of the orbicularis oris muscle. Furthermore, a decrease of the nasolabial angle can be observed because of maxillary retropositioning. Most techniques for lip shortening do not affect this angle. In this study, a treatment approach is proposed that addresses all of these signs of aging. METHODS: During a 1-year period, a procedure was performed on 10 patients using the following techniques: 1. transverse incision of the skin of the nasal floor and bilateral alar margin; 2. cutaneous detachment of the entire upper lip up to the mucocutaneous transition; 3. stabilization of the nostrils with a transcolumellar nylon stitch; 4. elevation of the released skin by elliptical skin resection at the alar margin and a trapezoid segment resection at the nasal floor; 5. use of nylon and absorbable sutures to approach the dermis and close the skin, respectively. RESULTS: Adequate results were observed in 9 of the 10 patients, characterized by shortening and projection of the upper lip, vermilion eversion, reduced incidence of rhagades, and improvements of the nasolabial angle. In 1 patient with unilateral paralysis of the lip, no significant correction of the asymmetry was achieved. CONCLUSIONS: The proposed "double duck" technique proved to be simple and effective, with successful resolution of nasolabial defects and effective concealment of scars INTRODUÇÃO: Durante o envelhecimento, o lábio superior sofre enrugamento, alongamento e inversão do vermelhão, em decorrência da ação esfinctérica do músculo orbicular dos lábios. Além disso, a retrusão da parede anterior da maxila provoca diminuição do ângulo nasolabial. A maioria das técnicas para encurtamento labial não obtém a abertura desse ângulo. Neste trabalho, é proposta uma abordagem que contemple o tratamento de todos esses sinais de envelhecimento. MÉTODO: No período de um ano, foram operados 10 pacientes pela seguinte técnica: 1. incisão transversa da pele do assoalho nasal e margem alar bilateral; 2. descolamento cutâneo de todo o lábio superior até a transição cutaneomucosa; 3. estabilização das asas nasais com ponto transcolumelar; 4. elevação da pele descolada, com ressecção elíptica do segmento justa-alar e trapezoide do segmento do assoalho nasal; e 5. suturas dérmica, com fio de náilon, e epidérmica, com fio absorvível. RESULTADOS: Encurtamento e projeção do lábio com eversão do vermelhão, diminuição das rágades e abertura do ângulo nasolabial adequados foram obtidos em 9 dos 10 pacientes. Em um paciente que apresentava paralisia unilateral do lábio, não houve correção significativa da assimetria. CONCLUSÕES: A técnica proposta mostrou-se de simples realização, de resolução efetiva dos objetivos e com boa ocultação das cicatrizes